Model-based interpretation of methane oxidation and respiration processes in landfill biocovers: 3-D simulation of laboratory and pilot experiments. (1st May 2020) - Ahmadi, Navid; Mosthaf, Klaus; Scheutz, Charlotte; Kjeldsen, Peter; Rolle, Massimo
Highlights: 3-D model for coupled flow, transport and reactive processes in landfill biocovers. Interaction between methane oxidation and respiration. Dynamics of gas transport in multicomponent mixtures. Interpretation of experimental datasets in laboratory column and pilot setups. Abstract: Landfill biocovers are an efficient strategy for the mitigation of greenhouse gas emissions from landfills. A complex interplay between key physical and reactive processes occurs in biocovers and affects the transport of gas components. Therefore, numerical models can greatly help the understanding of these systems, their design and optimal operation. In this study, we developed a 3-D multicomponent modeling approach to quantitatively interpret experimental datasets measured in the laboratory and in pilot-scale landfill biocovers. The proposed model is able to reproduce the observed spatial and temporal dynamics of CH4, O2 and CO2 migration in biocovers under different operating conditions and demonstrates the importance of dimensionality in understanding the propagation of gas flow and migration of gas components in such porous media. The model allowed us to capture the coupled transport behavior of gas components, to evaluate the exchange of gas fluxes at the interface between the biocover surface and free air flow, and to investigate the effects of different gas injection patterns on the distribution of gas components within biocovers. The model also helps elucidating the dynamics and competition between methane oxidation and respiration processes observed in the different experimental setups. The simulation outcomes reveal that increasing availability of methane (i.e., higher injection flow rates or higher fractions of CH4 in the injected gas composition) results in progressive dominance of methane oxidation in the biocovers and moderates the impact of respiration.